Islam Dibawa Masuk oleh Orang Nusantara: Dari Data Terserak Buzurgh Al-Ramahurmuzi, ‘Ajaibul Hind: Kisah-Kisah Ajaib di Daratan dan Lautan Hindi - Idris Masudi (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2020)
Studies of the archipelago (nusantara) on the notes of foreign travelers written in the 9th and 10th of centuries are still quite rare. Indeed, there have been several studies on the notes of travelers such as Ma Huan (China), Tome Pires (Portuguese), Ibn Bathuthah (Arabic), and some others. But, these studies revolve around the notes of travelers after the 10th of century. Meanwhile, notes of travelers who came to the archipelago (nusantara) in the century before 10 AD have not got serious attention yet. This book is a travel note's report which captures various activities in India, China and Southeast Asia. This book also contains a history about how Islam met in the Sarandib area. There are many interpretations of sarandib accurate location today. The findings of Keram Kevonian in his research on the names of regions in the Indian Ocean region using Armenian language sources stated that Sarandib means Swarnadipa which was no other than Sumatra. Keywords: nusantara, records of travelers, islamization, sarandib Reference: Balka, Ilyas. The Geoghraphy of The Islamic Word As Seen By Ibn Khaldun. Oman: Ministry of Awqaf and Religious Affairs, t.thn. Buzurg ibn Syahriyar Ramahurmuz. Kitab Ajayib al-Hind; Barruhu wa Bahruhu, wa Jazairuhu, Penerjemah: Arsyad Mokhtar. Malaysia: Pulau Pinang-Malaysia, 2015. Fatimi, S.Q. Islam Comes to Malaysia. Singapore: Malaysian Sociological Institute, 1963. —. Two Letters From Maharaja to The Khalifah: A Study in the Early History of Islam in the East. t.thn. Freeman-Grenville, G.S.P. “ Some Thought on Buzurg Ibn Shahriyar Al-Ramahormuzi: The Book of The Wonders India.” Paideuma Journal, 1982: no. 28. Hasymy, A. Sejarah masuk dan berkembangnya Islam di Indonesia. Bandung: Al-Maarif, 1981. Kevonian, Keram. Suatu Catatan Perjalanan di Laut Cina, dalam buku Lobu Tua Sejarah Awal Barus, editor Claude Gulliot, Jakarta: Yayasan Obor Indonesia, 2015. Jakarta: Yayasan Obor Indonesia, 2015. Kratovsky, Ignatius. Istoria Arabskoi Geograficheskio Literatury, Tarikh Al-Adab al-Jugrafi al-'Arabiy, penerjemah: Shalahuddin 'Utsman Hasyim,. Teheran: Al-Idarah al-Tsaqafah, t.thn. Nurcholis, Nanang. “The Golden Triangle (India-China-Indonesia) Maritime Cultural Relations (A Critical Analysis on Kitab ‘Ajaib alHind by Buzurg Ibn Shahriyār (d.399 H/1009 M).” Proceeding of the International Seminar and Conference 2015: The Golden Triangle (Indonesia-India-Tiongkok) Interrelations in Religion, Science, Culture, and Economic. Semarang: Unwahas, 2015. Ramahurmuz, Buzurg Ibn syahriyar. Kitab Ajaib al-Hind: Barruhu wa Bahruhu, wa Jaziruhu. Paris: Leiden-E.J. Brill, 1883. Shimada, Ryuoto. “Southeast Asia and International Trade: Continuity and Change in Historical Perspective.” Dalam Paths to the Emerging State in Asia and Africa Springer, oleh Keijiro Otsuka dan Kaoru Sugihara (Ed), Chapter III. Berlin: Springer, 2019. Syakir, Mahmud. al-Tarikh al-Islamy; al-Tarikh al-Muashirah fi al-Qarah al-Hindi. Beirut: al-Maktab al-Islamy, 1991.